Culturally shared metaphors expand contemporary concepts of resilience and post-traumatic growth: contrasting an indigenous Brazilian community and a Swiss rural community. Issue 4 (28th June 2018) - Meili, Iara; Heim, Eva; Maercker, Andreas
Abstract : The metaphorical concepts resilience and post-traumatic growth (PTG) reflect the contemporary Western understanding of overcoming highly challenging life events. However, it is known that across different cultures, a broad range of metaphorical idioms for describing adaptive responses to severe adversity exists. This study aimed to explore and contrast two distinct cultural groups' culturally shared metaphors for overcoming severe adversities. Fieldwork was conducted in two rural communities: an indigenous Brazilian community that has experienced severe collective adversity and a mountain village in Switzerland that has survived a natural disaster. We carried out separate qualitative metaphor analyses of semistructured interview data from each community. There were some similarities in the metaphorical narratives of the two cultural groups, for example, in metaphors of balance, changed perspective, collective cohesion and life as a journey . The main variations were found in metaphors of magical thinking, equilibrium and organic transformation used by the Brazilian group and metaphors of work, order and material transformation used by the Swiss group. Results from this study suggest that the Western-devised concepts of resilience and PTG can be further expanded, which is highlighted by the variety of culturally shared metaphors. Metaphorical idioms for overcoming severe adversity may be determined by the type of trauma as well as by the sociocultural and historical context. Our findings indicate potential approaches to the cultural adaptation of psychological interventions.